PENGARUH BAURAN PEMASARAN TERHADAP NIAT BERLANGGANAN KEMBALI HARIAN UMUM PIKIRAN RAKYAT DI KOTA BANDUNG - Sofyan Arief Fesa (Bina Ekonomi, 2015)
Pikiran Rakyat newspaper has the biggest market share in West Java, especially in Bandung city. However, the last five year data shows that there has been a decreasing trend in selling and subscription rate. Higher competition and domination of digital technology have been believed as the main factors that decrease the selling rate. The development of digital technology urges people to shift from paper-based newspaper to digital media such as, internet and e-paper, which are considered as effective and efficient; that enable readers to look for information that is based on categories. This article analyses the impacts of four types of marketing strategies (product, price, distribution, and promotion) on the customers’ intention to subscribe. Using 97 customers of Pikiran Rakyat newspaper as the respondents, this study concludes that those four marketing strategies have significant impact on the customers’ decision to re-subscribe. Keywords: Marketing mix, re-purchace, re-purchase intention, intention of re-subcribe.